1, 1′-Bi(2-naphthol-4, 5-dicarboximide)s: blue emissive axially chiral scaffolds with aggregation-enhanced emission properties. Issue 22 (16th October 2019) - Chen, Meng-Ting; Zhang, Yang; Vysotsky, Myroslav O.; Lindner, Joachim O.; Li, Meng-Hua; Lin, Mei-Jin; Würthner, Frank
Abstract : Novel electron-deficient 1, 1′-binaphthol derivatives bearing two dicarboximide groups at the peri -positions show intense blue luminescence and aggregation-enhanced emission characteristics. Abstract : 1, 1′-Binaphthol (BINOL) is a versatile chiral reagent with widespread applications in asymmetric catalysis and fluorescent bio-sensing and imaging. However, unsubstituted BINOLs exhibit only weak and short-wavelength emission, limiting their scope for the latter applications. Herein, we report axially chiral 1, 1′-bi(2-naphthol-4, 5-dicarboximide)s which show two reversible reductions, bright blue light fluorescence with fluorescence quantum yields up to 0.67, and aggregation-enhanced emission characteristics. Single crystal X-ray analysis revealed an intriguing double helical supramolecular polymer motif formed by π–π stacking interactions between 2-naphthol-4, 5-dicarboximide units. The enantiomers of racemic 1, 1′-bi(2-naphthol-4, 5-dicarboximide)s were resolved on chiral columns and studied by CD spectroscopy.